Non‐high‐density lipoprotein cholesterol independently predicts new onset of non‐alcoholic fatty liver disease. (14th October 2013) - Zelber‐Sagi, Shira; Salomone, Federico; Yeshua, Hanny; Lotan, Roni; Webb, Muriel; Halpern, Zamir; Santo, Erwin; Oren, Ran; Shibolet, Oren
Abstract Background & Aims Non‐alcoholic fatty liver disease (NAFLD) is associated with increased cardiovascular disease (CVD) risk. Non‐high‐density lipoprotein cholesterol (non‐HDL‐C), i.e. total cholesterol minus HDL, is a well‐established risk factor for CVD; however, its association with NAFLD development has not been established. Our aim was to test whether non‐HDL‐C is an independent predictor of new onset of NAFLD. Methods A prospective cohort study of 213 subjects from the general population, without liver disease, was studied. Evaluation of medical history, dietary and physical activity habits, fasting blood tests and ultrasonographic evidence of NAFLD was performed at baseline and after a 7‐year follow‐up by identical protocols. Results From 147 patients that did not have NAFLD at baseline, 28 (19%) developed NAFLD at the 7‐year follow‐up. The baseline levels of non‐HDL‐C were higher among subjects who developed NAFLD (179.5 ± 37.1 vs. 157.3 ± 35.1 mg/dl, P = 0.003). Non‐HDL‐C independently predicted new onset of NAFLD adjusting for age, gender, BMI or waist circumference, lifestyle and serum insulin (OR = 1.02 for every mg/dl increment, 1.01–1.04 95% CI, P = 0.008). Non‐HDL‐C was a stronger predictor for NAFLD than total cholesterol, low‐density lipoprotein cholesterol, triglycerides and HDL. No patients with non‐HDL‐C < 130 mg/dl developed NAFLD, whereas 20.8% of those with values between 130 to 160 and 24.6% of those with values >160 mg/dl developed NAFLD (P for trend = 0.015). Conclusions Non‐HDL‐C is an independent predictor for NAFLD and a stronger predictor than other lipoproteins. This association may stem from the combined hepato‐toxic effect of non‐HDL‐C and may explain the association between NAFLD and CVD.